Research on Policy Control of IP Flow Mobility Between LTE and WLAN - Xiao Shen; Zhen Shao; Chen Liu (Dianxin kexue)
3GPP standards about LTE and WLAN network integration and ANDSF were introduced，and the possibilities of a11 types of policy contro11ed handover between LTE and WLAN，using ANSDF，had been inquired into，including network architecture，policy type definition，combined policy analysis，etc.